2004
DOI: 10.1161/01.res.0000150368.56660.4f
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor Agonists Suppress Vascular Smooth Muscle Cell Proliferation and Inhibit Neointima Formation in Balloon-Injured Rat Carotid Arteries

Abstract: Abstract-The liver X receptors ␣ and ␤ (LXR␣ and LXR␤) are important regulators of cholesterol homeostasis in liver and macrophages. Synthetic LXR ligands prevent the development of atherosclerosis in murine models; however, the potential functional relevance of LXRs in vascular smooth muscle cells (VSMCs) has not been investigated. In the present study, we demonstrate that LXRs are expressed and functional in primary human coronary artery VSMCs (CASMCs). LXR ligands inhibited mitogen-induced VSMC proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 79 publications
11
90
0
1
Order By: Relevance
“…In spite of its undesirable side effects, T0901317 is still a popular reagent for LXR signaling-related research. Administration of the LXR agonist T0901317 in mouse disease models was reported to be effective for treatment of atherosclerosis, diabetes, Alzheimer's disease, and cancer [9][10][11][12][13][14][15]. The concentration of T0901317 to exhibit these therapeutic effects in vitro range between 1-10 μM [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of its undesirable side effects, T0901317 is still a popular reagent for LXR signaling-related research. Administration of the LXR agonist T0901317 in mouse disease models was reported to be effective for treatment of atherosclerosis, diabetes, Alzheimer's disease, and cancer [9][10][11][12][13][14][15]. The concentration of T0901317 to exhibit these therapeutic effects in vitro range between 1-10 μM [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…T0901317 is the most commonly used LXR agonist for investigating physiological roles of the LXRs. Treatment with T0901317 has been reported to improve several disease murine models, including lowering of serum and liver cholesterol level, inhibition of atherosclerosis development, stimulation of insulin secretion, improvement of glucose tolerance, activation of anti-inflammatory effects, and reduction of amyloid beta production related to Alzheimer's disease [9][10][11][12][13][14]. Recently, we reported that T0901317 suppressed growth of prostate tumors in athymic mice [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GW3965 exerted an effect similar to T1317 (results not shown). It has been reported that LXR agonists suppress proliferation of different cell types [17,18]. To further examine the effects of LXR activation on pancreatic beta cell growth, two different methods were used.…”
Section: Lxr Activation Inhibits Pancreatic Beta Cell Proliferationmentioning
confidence: 99%
“…Previous studies have reported that levels of LXRα and LXRβ are elevated in the pancreatic beta cells of rodent models of type 2 diabetes and these receptors have been implicated as important regulators of glucose and insulin metabolism [14][15][16]. In addition, it has been recently reported that activation of LXRs by T0901317 (T1317), a synthetic agonist, inhibits the proliferation of cancer cells [17] and vascular smooth muscle cells [18], partially through p27 protein level upregulation. However, the role of LXRs in the regulation of pancreatic beta cell proliferation is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…39 Human CRP cDNA was obtained from Dr Alok Agrawal (East Tennessee State University, Johnson City). Blots were cohybridized with human GAPDH cDNA (SigmaAldrich) to assess equal loading of samples.…”
Section: Rna Isolation and Northern Blottingmentioning
confidence: 99%